MTORC1‐PGC1 axis regulates mitochondrial remodeling during reprogramming. (18th August 2019) - Wang, Lulu; Xu, Xueting; Jiang, Che; Ma, Gang; Huang, Yinghua; Zhang, Hui; Lai, Yiwei; Wang, Ming; Ahmed, Tanveer; Lin, Runxia; Guo, Wenjing; Luo, Zhiwei; et al.
Abstract : Mitochondrial remodeling is a key early event during somatic cell reprogramming to induced pluripotent stem cells. It remains controversial whether mitophagy is the main reason for mitochondrial remodeling in reprogramming. By applying mito‐QC detection and statistical analysis in different reprogramming conditions, we show that mitophagy induction is not necessary for mouse reprogramming. We also provide further evidence that the mTORC1‐PGC1 pathway is the major player in this process. Abstract : Metabolic reprogramming, hallmarked by enhanced glycolysis and reduced mitochondrial activity, is a key event in the early phase of somatic cell reprogramming. Although extensive work has been conducted to identify the mechanisms of mitochondrial remodeling in reprogramming, many questions remain. In this regard, different laboratories have proposed a role in this process for either canonical (ATG5‐dependent) autophagy‐mediated mitochondrial degradation (mitophagy), noncanonical (ULK1‐dependent, ATG5‐independent) mitophagy, mitochondrial fission or reduced biogenesis due to mTORC1 suppression. Clarifying these discrepancies is important for providing a comprehensive picture of metabolic changes in reprogramming. Yet, the comparison among these studies is difficult because they use different reprogramming conditions and mitophagy detection/quantification methods. Here, we have systematically explored mitochondrial remodeling in reprogramming using different culture media and reprogramming factor cocktails, together with appropriate quantification methods and thorough statistical analysis. Our experiments show lack of evidence for mitophagy in mitochondrial remodeling in reprogramming, and further confirm that the suppression of the mTORC1‐PGC1 pathway drives this process. Our work helps to clarify the complex interplay between metabolic changes and nutrient sensing pathways in reprogramming, which may also shed light on other contexts such as development, aging and cancer.